Use of Herbal Medicinal Products among Children - Marda Sakinah (Eureka Herba Indonesia, 2023)
The use of herbal medicinal products for the treatment and prevention of diseases has a long tradition over the world. The herbal medicinal products are defined as exclusively herbal active substances-contained medicinal products which used for prevention or treatment of disease. Because of its process, it chemically different defined substances in several aspects; mostly because they consist of complex multi-component mixtures which from the extraction of plant parts such as roots and leaves. Many substances could be used for relieving clinical symptoms among children. The perception that “natural” products are harmless is still dominant in many consumers. Therefore, adverse effects of herb medicines are rarely reported by patients who have taken them.4 This review will discuss about use of herbal medicinal products and what is the impact for using this in children.